PENERAPAN METODE PENYULUHAN PERTANIAN PADA PETANI PADI SAWAH DI KELURAHAN TARATARA TIGA KECAMATAN TOMOHON BARAT KOTA TOMOHON (Application of Agricultural Extension Methods on Rice Farmers In Taratara Tiga Kelurahan West Tomohon Sub District Tomohon City) - Alexander D. J. Landasan; Melsje J. Memah; Martha M. Sendow (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this study is to  understand the application of the Agricultural Extension Methods on rice farmers in Kelurahan Taratara Tiga  WestTomohon  Sub District Tomohon City. The study is carried out in October to December 2020, with data used in primary adn secondary data then descriptive analysis.The research result showed that the application of agricultural extension methods on rice farmersin Taratara Tiga Kelurahan WestTomohon  Sub District Tomohon City, the individual method of applying agricultural counseling worked well enough with a 59.2 percent percentage. The group application of agricultural counseling worked well with 57.0 percent percentage and a method of mass-application of agricultural training result quite well with 58.6 percent percentage.